2022
DOI: 10.1021/acschembio.2c00163
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Bifunctional Drimenol Synthases of Marine Bacterial Origin

Abstract: Natural drimane-type sesquiterpenes, including drimenol, display diverse biological activities. These active compounds are distributed in plants and fungi; however, their accumulation in bacteria remains unknown. Consequently, bacterial drimane-type sesquiterpene synthases remain to be characterized. Here, we report five drimenol synthases (DMSs) of marine bacterial origin, all belonging to the haloacid dehalogenase (HAD)-like hydrolase superfamily with the conserved DDxxE motif typical of class I terpene synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 55 publications
0
25
0
Order By: Relevance
“…These findings suggest that there is more biosynthetic diversity than what is currently known for bacterial diterpenoids, e.g., ent -CPP may not always be transformed into the polycyclic kauranes, atisanes, and pimaranes of currently known bacterial diterpenoids. Add this to the recent discoveries of a monodomain type II TS from cyanobacteria 55 and a bifunctional sesqui-TS that belongs to the haloacid dehalogenase-like hydrolase superfamily 56 and the terpenoid biosynthetic potential of bacteria is likely severely underestimated.…”
Section: Resultsmentioning
confidence: 99%
“…These findings suggest that there is more biosynthetic diversity than what is currently known for bacterial diterpenoids, e.g., ent -CPP may not always be transformed into the polycyclic kauranes, atisanes, and pimaranes of currently known bacterial diterpenoids. Add this to the recent discoveries of a monodomain type II TS from cyanobacteria 55 and a bifunctional sesqui-TS that belongs to the haloacid dehalogenase-like hydrolase superfamily 56 and the terpenoid biosynthetic potential of bacteria is likely severely underestimated.…”
Section: Resultsmentioning
confidence: 99%
“…TcNudix1, a Nudix hydrolase from Tanacetum cinerariifolium, removes the terminal phosphate group of chrysanthemyl diphosphate in chrysanthemol biosynthesis; RhNUDX1 converts geranyl diphosphate into geranyl monophosphate to facilitate scent production in rose. , Thus, this clustering implicated A0A2P2GK84 and F8JSS1 as monofunctional class II TCs that provide cyclized prenyl diphosphates for subsequent hydrolysis, as seen in drimenol biosynthesis by AoDMS and AcDMS (Figure b). , In addition, these two enzymes share 57 and 64% sequence identity and similarity with each other, respectively, but show very low sequence identity (<20%) with any of the known DMSs of fungi or plant origin (Table S3). Therefore, we prioritized these two putative STCs for functional characterization.…”
Section: Resultsmentioning
confidence: 99%
“…A marine bacterial HAD-like DMS was discovered from Aquimarina spongiae (AsDMS) using AoDMS as a genetic beacon during the preparation of this manuscript. 20 In this study, we identified two DPP synthases from Streptomyces showdoensis and Streptomyces cattleya, SsDMS and ScDMS, respectively. Structural characterization of SsDMS using X-ray crystallography led to the determination that these enzymes possess the well-known βγ-didomain structure of canonical class II TCs, an architecture previously unseen in STCs (Figure 1c).…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[55,56] These findings suggest that there is more biosynthetic diversity than what is currently known for bacterial diterpenoids, e.g., ent-CPP may not always be transformed into the polycyclic kauranes, atisanes, and pimaranes of currently known bacterial diterpenoids. Add this to the recent discoveries of a monodomain type II TS from cyanobacteria [57] and a bifunctional sesqui-TS that belongs to the haloacid dehalogenase-like hydrolase superfamily [58] and the terpenoid biosynthetic potential of bacteria is likely severely underestimated.…”
Section: Bioinformatics Analysis Of Type II Tss Highlights Terpenoid ...mentioning
confidence: 99%